Effects of ultrasound and microwave pretreatments of carrot slices before drying on the color indexes and drying rate - Fakhreddin Salehi; Kimia Goharpour; Helia Razavi Kamran (Ultrasonics Sonochemistry, 2023)
The aim of this study was to examine the impacts of microwave pretreatment (MWP) and ultrasonic pretreatment (USP) on drying time (DT), mass transfer kinetics, effective water diffusivity (Deff), rehydration rate, color index (L*, a*, b*), and the surface shrinkage of carrot slices when dried in a hot air dryer (70 °C). The microwave process was performed for 0, 15, 30, 45, and 60 s before drying of carrot slices. In addition, the ultrasound process was performed in an ultrasonic bath (40 kHz and 150 W) for 0, 5, 10, 15, and 20 min. The results confirmed that the MWP and USP decreased the DT (higher water loss) of carrot slices. Deff values for microwave-pretreated slices were considerably higher than those for nontreated carrot slices (p < 0.05). The Deff calculated by Fick's second law was increased from 8.69 × 10−10 to 10.96 × 10−10 m2 s−1, and from 7.56 × 10−10 to 9.39 × 10−10 m2 s−1, for samples pretreated by microwave and ultrasound, respectively. The empirical value for the drying curves were fitted to the common thin film-equations, and Page's equation was the most suitable to describe the dehydration rate of carrot slices. The average rehydration ratio of nontreated, microwave-treated, and ultrasound-treated carrot slices were 432.3 %, 449.2 %, and 360.9 %, respectively. The redness, yellowness, and surface shrinkage parameters of pretreated samples by microwave were higher than the nontreated slices. The lightness and redness parameters of pretreated carrot slices by ultrasound were higher than the nontreated samples under all conditions.